Development of antidandruff shampoo from the fermented product of Ocimum sanctum Linn. - Chanun Punyoyai (2018)
© 2018 by the authors. This study aimed to investigate Malassezia furfur inhibitory activity of the fermented product from Ocimum sanctum and develop an antidandruff shampoo. The fermented product was obtained by the fermentation process of the aerial part of O. sanctum. Total soluble protein was detected in the fermented product with the amount of 65.32 ± 0.14 mg/100 mL, whereas there was no organic acid. The inhibitory activity against four strains of M. furfur (No. 133, 656, 6000, and 7966) of the fermented product and shampoos containing the fermented product were investigated by broth dilution and agar diffusion method, respectively. The fermented product possessed high antifungal activity with the minimum inhibitory concentrations for 50% (MIC50) of M. furfur 133, 656, 6000, and 7966 of 0.125, 0.25, 0.125, and 0.125 mg/mL, respectively. Interestingly, the antifungal activity against M. furfur 656 was comparable to that of ketoconazole. Shampoo formulation C, which was the best formulation in terms of characteristics and stability, obtained a high level of satisfaction scores in terms of hair smoothness, hair shine, ease in combing, frizz reduction, and triboelectric reduction while brushing. Additionally, the shampoo containing 2% (w/w) of the fermented product of O. sanctum also possessed inhibitory activity against M. furfur 133, 656, 6000, and 7966 with inhibition zones of 13.2 ± 1.6, 12.8 ± 1.1, 18.7 ± 0.3, and 17.0 ± 1.1 mm respectively. Therefore, this shampoo was suggested for use as an antidandruff shampoo.